Finance and Development, June 2010. (Finance and Development; Finance and Development ;, 2010)
Asia Leading the Way explores how the region is moving into a leadership role in the world economy. The issue looks at Asia's biggest economy, China, which has relied heavily on exports to grow, and its need to increase domestic demand and to promote global integration if it is to continue to thrive. China is not the only Asian economy that heavily depends on exports and all of them might take some cues from the region's second-biggest economy, India, which has a highly developed services sector. Min Zhu, the new Special Advisor to the IMF's Managing Director, talks about Asia in the global economy, the global financial crisis, correcting imbalances, and the IMF in Asia. And "People in Economics" profiles an Asian crusader for corporate governance, Korea's Jang Hasung. This issue of F and D also covers how best to reform central banking in the aftermath of the global economic crisis; the pernicious effects of derivatives trading on municipal government finances in Europe and the United States; and some ominous news for governments hoping to rely on better times to help them reduce their debt burdens. Mohamed El-Erian argues that sovereign wealth funds are well-placed to navigate the new global economy that will emerge following the world wide recession. "Back to Basics" explains supply and demand. "Data Spotlight" explores the continuing weakness in bank credit. And "Picture This" focuses on the high, and growing, cost of energy subsidies.